Determinants of Firms' Backward- and Forward-Looking R&D Search Behavior - Chen, Wei-Ru (Organization Science, 2008)
This study develops and operationalizes a behavioral forward-looking search model by incorporating prospect theory, organizational risk literature, and the logic of the behavioral theory of the firm. With recognition of the bounded rationality of decision makers and the goal-directed, rule-based nature of organizations, this model suggests that a comparison between firms' performance expectation and performance target translates the cognitive representation of the firms' future into their subsequent actions. By examining the research and development (R&D) expenditures of U.S. manufacturing firms from 1980 to 2001, this study explores how performance, aspirations, expectations, and slack affect decision making about firms' R&D search investments. The findings show that both performance feedback and performance prospect are important determinants of firms' search behavior after controlling for firm, industry, and time effects. In addition, backward- and forward-looking determinants have interactive effects on search behavior. Firms' problem-driven search activity further increases when firms feel unlikely to achieve the performance target for another year. In contrast, search intensity is reduced when firms expect to improve their performance from an underperforming situation to an outperforming situation. The findings suggest that future research on performance feedback and experiential learning should also consider the effect of forward-looking prospects on firm behavior.